H2S priming and plant abiotic stress tolerance - Silveira, Neidiquele Maria [UNESP]; Hancock, John Travers; Machado, Eduardo Caruso; Ribeiro, Rafael Vasconcelos (Elsevier, 2023)
Hydrogen sulfide (H2S) is an emerging multitasking signaling molecule involved in plant responses to many abiotic stresses, promoting tolerance and growth under limiting conditions. There is experimental evidence of cross talk between H2S and nitric oxide, another important signaling molecule with key roles in stress tolerance. This chapter reviews the current knowledge about how H2S modulates physiological and biochemical responses and improves plant acclimation to various environmental stresses, such as drought, flooding, heavy metals, salinity, and temperature extremes. The most used H2S donors are also addressed. Finally, an overview is provided of the major roles of H2S in higher plants, focusing on its benefits and potential biotechnological applications.
Keywords: Environmental stress; H2S donor; Signaling molecule; Stress tolerance